The Rise and Persistence of Illegal Crops: Evidence from a Naive Policy Announcement - Prem, Mounu; Vargas, Juan F.; Mejía, Daniel (The Review of Economics and Statistics, 2023)
Abstract Policies based on prohibition and repression to fight the war on drugs have largely failed in a variety of contexts. However, incentive-based policies may also fail and have unintended negative consequences if policymakers do not properly anticipate behavioral reactions. This is an particularly important concern in the case of policies announced prior to their implementation. In this paper, we show that a naive and untimely policy announcement generated an unprecedented escalation in cocaine production in Colombia, offsetting almost 20 years and billions of dollars of U.S.-backed efforts to stop drug production and cartel action.